2012
DOI: 10.1093/icvts/ivs212
|View full text |Cite
|
Sign up to set email alerts
|

In patients with carcinoid syndrome undergoing valve replacement: will a biological valve have acceptable durability?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'In patients with carcinoid syndrome undergoing valve replacement, will a biological valve have acceptable durability?' Altogether, more than 130 papers were found using the reported search, of which 17 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…In a recent review, Mabvuure et al [8] dealt with this question. In their analysis of 17 series with CHD patients who had undergone surgical biological tricuspid valve replacement, they reported a 30-day mortality approaching 20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Mabvuure et al [8] dealt with this question. In their analysis of 17 series with CHD patients who had undergone surgical biological tricuspid valve replacement, they reported a 30-day mortality approaching 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most valves at that time appeared normal on echocardiography or autopsy. From these results, the authors suggested that biological valves have an acceptable lifespan in CHD [8]. A strong argument to use biological valves - including the percutaneous SAPIEN valve - in CHD patients is the fact that they do not require long-term anticoagulation, a benefit that potentially avoids tumour bleeding complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…One patient with elevated gradients 3 months after the procedure died as a cause of his tumour disease. For those reasons, we as others, who comprised available data, believe that BP are an adequate alternative [12] .…”
Section: Secondary Endpointsmentioning
confidence: 99%
“…Carcinoid tumors arising in the bronchi may be associated with manifestations of carcinoid syndrome without liver metastases because their biologically active products reach the systemic circulation before passing through the liver and being metabolized.In most patients, there is an increased urinary excretion of 5-HIAA (5-hydroxyindoleacetic acid), a degradation product of serotonin.The biology of these tumors is interesting as it differs from many other tumor types. Ongoing research on the biology of these tumors may reveal new mechanisms for tumor development [9][10][11] .…”
Section: Droxy-tryptophanementioning
confidence: 99%